THE INFLUENCE OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE EMPLOYEES IN CORRECTIONAL INSTITUTIONS CLASS IIA ABEPURA - Induwek, Maria Rana; Kusmiyanti, Kusmiyanti (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the effect of work motivation on the performance of Class IIA Abepura Correctional Institution employees. The research method used is the quantitative research method. To obtain research data, questionnaires were distributed to 100 respondents who were officers of the Abepura Class IIA Correctional Institution. The questionnaire used was 40 questions related to the research variables. To analyze the research data using descriptive analysis techniques through simple linear tests, significance tests, and determination tests using IBM SPSS 27. The results of this study indicate the percentage of influence given by the work motivation variable on employee performance in the determination test, which shows that the work motivation variable as an independent variable has an influence of 43.8% on the performance of the dependent employee. Meanwhile, the hypothesis test obtained that there is an effect of work motivation on employee performance at the Class IIA Abepura Correctional Institution. Keywords: Motivation; Employee Performance; Correctional Institution